2020
DOI: 10.1371/journal.ppat.1008214
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica and pathogenesis: A calcium connection

Abstract: Calcium signaling plays a key role in many essential processes in almost all eukaryotic systems. It is believed that it may also be an important signaling system of the protist parasite Entamoeba histolytica. Motility, adhesion, cytolysis, and phagocytosis/trogocytosis are important steps in invasion and pathogenesis of E. histolytica, and Ca 2+ signaling is thought to be associated with these processes leading to tissue invasion. There are a large number of Ca 2+-binding proteins (CaBPs) in E. histolytica, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…PI(4,5)P 2 is further metabolized to DAG and inositol 3-phosphate (IP 3 ) by phospholipase C (PLC). IP 3 works as a trigger of Ca 2+ release and is involved in cytoskeletal remodeling [ 16 ], and is thus likely involved in erythrophagocytosis where Ca 2+ -dependent cytoskeletal reorganization plays a major role [ 17 , 18 ]. It was previously reported that E. histolytica has an IP 3 and IP 4 -dependent Ca 2+ release to the cytosol [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…PI(4,5)P 2 is further metabolized to DAG and inositol 3-phosphate (IP 3 ) by phospholipase C (PLC). IP 3 works as a trigger of Ca 2+ release and is involved in cytoskeletal remodeling [ 16 ], and is thus likely involved in erythrophagocytosis where Ca 2+ -dependent cytoskeletal reorganization plays a major role [ 17 , 18 ]. It was previously reported that E. histolytica has an IP 3 and IP 4 -dependent Ca 2+ release to the cytosol [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…E. histolytica exploits elaborate biological processes that contribute to its parasitism and pathogenesis, including motility, adherence, phago‐ and trogocytosis, cytotoxicity, defence against nutrient starvation, temperature changes, and host immune systems (Faust & Guillen, 2012; Marie & Petri Jr, 2014; Nakada‐Tsukui & Nozaki, 2016; Orozco, Guarneros, Martinez‐Palomo, & Sánchez, 1983; Ralston et al, 2014; Tavares et al, 2005; Tovy et al, 2011). All of these processes require coordinated regulation of signal transduction, cytoskeletal reorganization, and vesicular trafficking (Aguilar‐Rojas, Olivo‐Marin, & Guillen, 2016; Babuta, Bhattacharya, & Bhattacharya, 2020; Nozaki & Nakada‐Tsukui, 2006). Recent studies indicate in particular that trogo‐ and phagocytosis play a pivotal role in disease manifestations and host immune evasion (Miller, Suleiman, & Ralston, 2019; Nakada‐Tsukui & Nozaki, 2020; Ralston et al, 2014; Somlata, Nakada‐Tsukui, & Nozaki, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate in particular that trogo‐ and phagocytosis play a pivotal role in disease manifestations and host immune evasion (Miller, Suleiman, & Ralston, 2019; Nakada‐Tsukui & Nozaki, 2020; Ralston et al, 2014; Somlata, Nakada‐Tsukui, & Nozaki, 2017). It has been shown that both amebic trogo‐ and phagocytosis are energy dependent and require Gal/GalNAc lectin, protein and lipid kinases such as C2‐domain‐containing protein kinase (EhC2PK), atypical kinase (EhAK1), and phosphoinositide‐3‐kinase (PI3K), phosphatidylinositide‐binding proteins such as FYVE domain containing protein 4 (Nakada‐Tsukui, Okada, Mitra, & Nozaki, 2009) and SNXs (Watanabe, Nakada‐Tsukui, & Nozaki, 2020), and proteins involved in actin rearrangement such as calcium binding proteins, ArpA2/3, Rho/Rac, EhP3, and EhFP10 (Agarwal et al, 2019; Babuta et al, 2020; Babuta, Kumar, Gourinath, Bhattacharya, & Bhattacharya, 2018; Babuta, Mansuri, Bhattacharya, & Bhattacharya, 2015; Bharadwaj et al, 2018; Bharadwaj, Arya, Shahid Mansuri, Bhattacharya, & Bhattacharya, 2017; Gautam, Ali, Bhattacharya, & Gourinath, 2019; Nakada‐Tsukui et al, 2009; Powell et al, 2006; Ralston et al, 2014; Somlata, Bhattacharya, & Bhattacharya, 2011; Watanabe et al, 2020). EhAGC kinase 1 represents only protein that is known to be engaged with only trogocytosis, but not phagocytosis, whereas EhAGCK2 is involved in both processes, but on the different stages of target internalisation.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of kinase expression and overexpression of non-functional kinases lead to defects in phagocytosis ( Mansuri et al., 2014 ). Various experimental studies indicate EhAK1 to be downstream of EhC2PK, coupling Ca 2+ signalling and actin dynamics at the site of phagocytosis ( Babuta et al., 2020 ). Apart from these, a conserved AGCK family kinase, EhAGCK1, has been shown to be exclusively involved in trogocytosis.…”
Section: Cellular Drug Targetsmentioning
confidence: 99%
“…For example, CaBPs (calcium binding proteins), C2PK (C2 domain containing protein), EhAK1, APSK (an unconventional alpha kinase), etc. ( Mansuri et al., 2014 ; Babuta et al., 2020 ). Further, probiotics, drugs and small molecules which act on the gut microbiota and alter the parasite biology can prevent invasion and subsequent pathogenesis, thereby offering an interesting alternative for the treatment of amebiasis and other parasitic intestinal infections ( Burgess and Petri, 2016 ).…”
Section: Introductionmentioning
confidence: 99%